The Sharia Financial Literacy To Improve Understanding And Competitiveness Of Msmes In Gunung Putri Village: Literasi Keuangan Syariah Untuk Meningkatkan Pemahaman Dan Daya Saing Umkm Desa Gunung Putri - Fauzan Romadhian Khairi; Agus Putrono; Abdurrahman Hakim; Ahmad Royyan Firdaus; Siti Maryam (Jurnal Pengabdian Masyarakat (Bisma), 2025)
Abstract Sharia financial literacy is key to improving the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in rural areas, including Gunung Putri Village, Bogor Regency. This study aims to analyze the level of understanding of Sharia financial literacy, the impact of education on MSMEs' understanding, and formulate effective strategies to improve the competitiveness of MSMEs in Gunung Putri Village, Bogor Regency, West Java. Using a qualitative approach with case studies, data were collected through interviews, questionnaires, and observations of 50 MSMEs in Gunung Putri Village. The results indicate that the level of Sharia financial literacy among MSMEs in Gunung Putri Village is very low. Initial observation data showed that only 10 people (20%) understood the basic concepts of Sharia finance and 40 people (80%) did not understand the concept. Through the Sharia financial literacy education seminar, it has had a significant impact in increasing MSMEs' understanding of the concepts, products, and services of Sharia banking. To support and enhance the competitiveness of MSMEs in Gunung Putri Village, four relevant strategies have been formulated for adoption: collaboration between institutions, strengthening digitalization, empowering communities through PKK (Family Welfare Movement) and mosque-based training, and monitoring and evaluating activities at least once every six months. These four strategies are expected to help MSMEs in Gunung Putri Village enter the halal industry ecosystem, a business trend in this digital era. Keywords: Sharia Financial Literacy, MSMEs, Competitiveness, Gunung Putri Village, Halal Economic Education.